GENDER DIFFERENCES IN CHRONIC LOWER LIMB ISCHEMIA PRESENTATION AND REVASCULARIZATION OUTCOMES - Ricardo Correia; Joana Catarino; Isabel Vieira; Rita Bento; Rita Garcia; Fábio Pais; Tiago Ribeiro; Joana Cardoso; Rita Ferreira; Ana Garcia; Frederico Bastos Gonçalves; Maria Emília Ferreira (Angiologia e Cirurgia Vascular, 2021)
Introduction: Sex-specific data on outcomes after lower limb revascularization associate the female gender with worse surgical outcomes, particularly after open procedures. Women were found to be more likely to suffer from procedure complications, limb loss, and mortality than their male counterparts. This study aims to identify differences in demographic characteristics, clinical presentation and all major outcomes after lower limb revascularization between female and male patients.